Anti-cracking high-durability coating and preparation method thereof
By using activated composite bentonite and polyurethane acrylic resin in the coating, the problem of low self-repair performance of existing coatings is solved, and the effect of efficient repair of cracks of different sizes and extending the coating life is achieved.
Patent Information
- Application Number
- CN202411401047.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing self-repair coatings have low self-repair performance, are prone to re-erosion, and cannot effectively repair cracks of different sizes, resulting in insufficient durability of the coating.
Self-healing microcapsules prepared by activated composite bentonite and polyurethane acrylic resin as core material and modified urea-formaldehyde resin as wall material. As filler for epoxy resin, the stability of bentonite is enhanced by using nanotitanium dioxide column-supported structure, and photocatalytics The core material is cured under ultraviolet light to achieve better repair results.
It significantly improves the crack resistance and durability of the paint, can effectively repair cracks of different sizes, extend the service life of the coating, and further improves the performance of the paint through the function of photocuring and adsorbing pollutants.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a crack-resistant and highly durable coating and a preparation method thereof. Background Art
[0002] As a coating material that plays a protective and decorative role, paint is widely used in industrial production, construction and all aspects of daily life. However, due to certain factors, some small gaps will appear on the surface of the coating. These gaps will gradually become larger when exposed to air, moisture and other environments for a long time, eventually causing the coating to fall off the surface of the substrate, greatly reducing the protective life of the coating. In order to increase the life of the coating, it is usually extended by adding various additives, but this method is costly, ineffective, and prone to pollution, which is contrary to the purpose.
[0003] There are some self-healing coatings in the related art, which can repair the coating to a certain extent without the need for additional repair materials. A commonly used self-healing coating can release a repair agent, which can be divided into microcapsule-type self-healing coatings, hollow fiber self-healing coatings, etc. When the coating matrix is damaged, the repair agent in the capsule or hollow fiber can be released, fill the cracks and solidify, thereby playing a repair role. However, the self-healing microcapsules of current technology have low performance and are easily corroded for the second time. On the other hand, they cannot adapt to cracks of different sizes, so the effect is not good. Summary of the invention
[0004] The purpose of the present invention is to provide a crack-resistant and highly durable coating and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a crack-resistant and highly durable coating, wherein the coating is made of homemade self-repairing microcapsules added as fillers into epoxy resin.
[0006] Furthermore, the self-made self-repairing microcapsules are prepared by using activated composite bentonite and polyurethane acrylic resin as core materials and modified urea-formaldehyde resin as wall materials to prepare microcapsules with self-repairing effects.
[0007] Furthermore, the modified urea-formaldehyde resin is obtained by adding oxidized activated carbon to urea-formaldehyde resin.
[0008] Furthermore, a method for preparing a crack-resistant and highly durable coating comprises the following preparation steps:
[0009] (1) Add butyl titanate to anhydrous ethanol, stir at 500 rpm for 1 hour to mix evenly to form a butyl titanate / ethanol solution, then dropwise add the butyl titanate / ethanol solution to a nitric acid aqueous solution, vigorously stir at 3000 rpm for 20 minutes to allow a mixing reaction; adjust the pH to 1-3 with a 1 mol / L sodium hydroxide aqueous solution, and stir at 500 rpm for 30 minutes to obtain a mixed solution; take bentonite, fully soak it with deionized water at a mass ratio of 1:1, , add it to the mixed solution, stir at 500rpm for 2h, filter it to separate the solid and liquid, wash the solid with deionized water for 3-5 times, and then dry it at 60℃ for 5h; then calcine at 400-700℃ for 4h, cool at room temperature and crush it again to 20-50μm to prepare nano-titanium dioxide pillared composite bentonite; then heat the composite bentonite to 200-250℃ under the protection of nitrogen, activate it for 1-3h, and prepare activated composite bentonite;
[0010] (2) Mixing nano-activated carbon and nitric acid aqueous solution at a solid-liquid ratio of 1:2-4 and refluxing for 5 hours, washing with deionized water for 3 times after the reaction, and then drying in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; taking polyurethane acrylic resin and activated composite bentonite at a mass ratio of 1:1-3, mixing them at a speed of 150 rpm for 10 minutes, adding 0.5-1.5 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; preparing an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, and then slowly adding the repair solution to the aqueous solution, the mass ratio of the repair solution to the aqueous solution is 1-2:10, stirring at a speed of 800 rpm for 40 minutes to form a uniform solution. A uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40wt% in a molar ratio of 1:2, a sodium hydroxide aqueous solution with a concentration of 6mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then the mixture is magnetically stirred at 70°C for 1h at a stirring speed of 400rpm, and 0.5-1.5wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1-2, and 3wt% of m-diphenol and 5wt% of ammonium chloride are added, and then the temperature is slowly raised to 50-60°C, and after reacting for 3-5h, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12h to obtain self-healing microcapsules;
[0011] (3) The self-healing microcapsules were added to WSR618 epoxy resin at a specified mass fraction of 1 to 10%, and then DETA curing agent and aminopropyl triethoxysilane were added. After stirring at 250 rpm for 20 min, the bubbles were vacuum degassed at 0.085 MPa to obtain a crack-resistant and highly durable coating.
[0012] Furthermore, the concentration of the nitric acid aqueous solution in step (1) is 1 mol / L.
[0013] Furthermore, in the step (1), the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:6 to 16:1.4.
[0014] Furthermore, in step (1), the molar ratio of bentonite to butyl titanate is 5 to 15:1.
[0015] Furthermore, the concentration of the nitric acid aqueous solution in step (2) is 7 mol / L.
[0016] Furthermore, in the aqueous solution of sodium dodecylbenzenesulfonate, urea and polyvinyl alcohol in step (2), the concentration of sodium dodecylbenzenesulfonate is 2 wt %, the concentration of urea is 0.5 wt %, and the concentration of polyvinyl alcohol is 0.4 wt %.
[0017] Furthermore, in the step (3), the mass ratio of epoxy resin, DETA curing agent and aminopropyltriethoxysilane is 25:2:0.4-0.8.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The self-repairing microcapsules prepared by the present invention are added as fillers into epoxy resin to prepare coatings, so as to achieve the effects of anti-cracking and high durability.
[0020] Firstly, a microcapsule with self-repairing effect is prepared by using activated composite bentonite and polyurethane acrylic resin as core materials and modified urea-formaldehyde resin as wall materials, and then added into the coating as filler; when the coating is subjected to aging or external force to produce fine cracks, the wall material modified urea-formaldehyde resin cracks to release the core material therein for repair; the composite bentonite is supported by nano-titanium dioxide pillars in the interlayer structure of the bentonite, which can make the bentonite more stable to prevent further cracking, and on the other hand, it acts as a photocatalyst to catalyze the polyurethane acrylic resin from the inside, so that the core material is released and irradiated with external ultraviolet rays for curing; during the slow curing, titanium dioxide can absorb and decompose other organic pollutants, and at the same time, the bentonite will expand to a certain extent due to contact with water molecules in the air, and fit fine cracks of different sizes to a greater extent; the activated bentonite chemically combines with the light-curing polyurethane acrylic resin due to the hydroxyl groups on the surface, and then combines with the layered structure of the bentonite due to curing and cross-linking, forming a stable and seamless repair agent, so that the coating has a self-repairing effect, thereby improving the durability of the coating;
[0021] Secondly, the modified urea-formaldehyde resin is prepared by adding oxidized nano-activated carbon into the urea-formaldehyde resin. The active groups produced by oxidation can react with the hydroxymethyl groups in the urea-formaldehyde resin to increase the cross-linking degree of the resin. The activated carbon can not only adsorb free formaldehyde during the preparation process, but also make the urea-formaldehyde resin wall material have a light-shielding effect, so that the microcapsule core material can be photocured and cross-linked after being released. Finally, a silane coupling agent is used to improve the dispersibility of the self-healing microcapsules so that they are evenly distributed in the coating with epoxy resin as the raw material, thereby improving the coating's anti-cracking performance. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a crack-resistant and highly durable coating prepared in the following examples are as follows:
[0024] Cracking resistance: The coatings obtained in the examples and comparative examples were uniformly coated on the surface of the glass substrate, with a coating amount of 100 g / m 3 After drying and curing, place it outdoors for 30 days and observe the surface cracks.
[0025] Self-repairing property: The coatings obtained in the examples and comparative examples were uniformly coated on the surface of the glass substrate, with a coating amount of 100 g / m 3 After drying and curing, rub the coating surface with a 15N scratching component to scratch the entire coating surface. Take the coating area as the initial scratch damage area S1. After placing it outdoors for 5 days, measure the scratch damage area S2 after treatment, and calculate the self-repair efficiency according to the formula 100% × (S1-S2) / S1.
[0026] Example 1
[0027] (1) Add butyl titanate to anhydrous ethanol, stir at 500 rpm for 1 hour to mix uniformly to form a butyl titanate / ethanol solution, then dropwise add the butyl titanate / ethanol solution into a 1 mol / L nitric acid aqueous solution, wherein the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:6:1.4, and stir vigorously at 3000 rpm for 20 minutes to react; adjust the pH to 1 with a 1 mol / L sodium hydroxide aqueous solution, and stir at 500 rpm for 30 minutes to obtain a mixed solution; take bentonite, and remove After being fully infiltrated with ionized water at a mass ratio of 1:1, it is added to the mixed solution so that the molar ratio of bentonite to butyl titanate is 5:1, and stirred at 500rpm for 2h, and then filtered to separate the solid and liquid, and the solid is washed with deionized water for 3 times, and then dried at 60°C for 5h; then calcined at 400°C for 4h, and then pulverized again after cooling at room temperature to 20μm to prepare nano-titanium dioxide pillared composite bentonite; then, under the protection of nitrogen, the composite bentonite is heated to 200°C and activated for 1h to prepare activated composite bentonite;
[0028] (2) Mixing nano-activated carbon and a 7 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:2, reflux reaction for 5 hours, washing with deionized water for 3 times after the reaction, and then drying in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; taking polyurethane acrylic resin and activated composite bentonite in a mass ratio of 1:1, stirring at a speed of 150 rpm for 10 minutes, adding 0.5 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; preparing an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, wherein the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2 wt%, the concentration of urea is 0.5 wt%, and the concentration of polyvinyl alcohol is 0.4 wt%, and then slowly adding the repair solution to the aqueous solution, the repair solution and the aqueous solution are mixed. The mass ratio of urea to formaldehyde was 1:10, and the mixture was stirred at 800 rpm for 40 min to form a uniformly dispersed water-in-oil core material; urea and formaldehyde were prepared into a mixed aqueous solution with a concentration of 40 wt% according to a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L was added to adjust the pH of the mixed aqueous solution to 8, and then the mixture was magnetically stirred at 70°C for 1 h, and the stirring speed was 400 rpm. 0.5 wt% of oxidized nano-activated carbon was added while stirring to form a prepolymer; the prepolymer was added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid was 1:1, and 3 wt% of m-diphenol and 5 wt% of ammonium chloride were added, and then the temperature was slowly raised to 50°C. After reacting for 3 h, the solid was carefully taken out, washed twice with deionized water, and dried at room temperature for 12 h to obtain self-healing microcapsules;
[0029] (3) The self-healing microcapsules were added to WSR618 epoxy resin at a specified mass fraction of 1%, and then DETA curing agent and aminopropyl triethoxysilane were added. The mass ratio of epoxy resin, DETA curing agent and aminopropyl triethoxysilane was 25:2:0.4. After stirring at 250 rpm for 20 min, the anti-cracking and high-durability coating was prepared by vacuum degassing at 0.085 MPa.
[0030] Example 2
[0031] (1) Add butyl titanate to anhydrous ethanol, stir at 500 rpm for 1 hour to mix uniformly to form a butyl titanate / ethanol solution, then dropwise add the butyl titanate / ethanol solution into a 1 mol / L nitric acid aqueous solution, wherein the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:11:1.4, and stir vigorously at 3000 rpm for 20 minutes to react; adjust the pH to 2 with a 1 mol / L sodium hydroxide aqueous solution, and stir at 500 rpm for 30 minutes to obtain a mixed solution; take bentonite, and remove After being fully infiltrated with ionized water at a mass ratio of 1:1, it is added to the mixed solution so that the molar ratio of bentonite to butyl titanate is 10:1, and stirred at 500 rpm for 2 hours, and then filtered to separate the solid and liquid, and the solid is washed with deionized water for 4 times, and then dried at 60°C for 5 hours; then calcined at 550°C for 4 hours, and then pulverized again after cooling at room temperature to 35μm to prepare nano-titanium dioxide pillared composite bentonite; then, under the protection of nitrogen, the composite bentonite is heated to 225°C and activated for 2 hours to prepare activated composite bentonite;
[0032] (2) Mixing nano-activated carbon and a 7 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:3, reflux reaction for 5 hours, washing with deionized water for 3 times after the reaction, and then drying in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; taking polyurethane acrylic resin and activated composite bentonite in a mass ratio of 1:2, stirring at a speed of 150 rpm for 10 minutes, adding 1wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; preparing an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, wherein the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2wt%, the concentration of urea is 0.5wt%, and the concentration of polyvinyl alcohol is 0.4wt%, and then slowly adding the repair solution to the aqueous solution, the repair solution and the aqueous solution are mixed. The mass ratio is 1.5:10, and the mixture is stirred at 800 rpm for 40 minutes to form a uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40wt% according to a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then the mixture is magnetically stirred at 70°C for 1 hour at a stirring speed of 400 rpm, and 1wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1.5, and 3wt% of m-diphenol and 5wt% of ammonium chloride are added, and then the temperature is slowly raised to 55°C. After reacting for 4 hours, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12 hours to obtain self-healing microcapsules;
[0033] (3) The self-healing microcapsules were added to WSR618 epoxy resin at a specified mass fraction of 5%, and then DETA curing agent and aminopropyl triethoxysilane were added. The mass ratio of epoxy resin, DETA curing agent and aminopropyl triethoxysilane was 25:2:0.6. After stirring at 250 rpm for 20 min, the anti-cracking and high-durability coating was prepared by vacuum degassing at 0.085 MPa.
[0034] Example 3
[0035] (1) Add butyl titanate to anhydrous ethanol, stir at 500 rpm for 1 hour to mix uniformly to form a butyl titanate / ethanol solution, then dropwise add the butyl titanate / ethanol solution into a 1 mol / L nitric acid aqueous solution, wherein the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:16:1.4, and stir vigorously at 3000 rpm for 20 minutes to react; adjust the pH to 3 with a 1 mol / L sodium hydroxide aqueous solution, and stir at 500 rpm for 30 minutes to obtain a mixed solution; take bentonite, and remove After being fully infiltrated with ionized water at a mass ratio of 1:1, it was added to the mixed solution so that the molar ratio of bentonite to butyl titanate was 15:1, and stirred at 500rpm for 2h, and then filtered to separate the solid and liquid, and the solid was washed with deionized water for 5 times, and then dried at 60°C for 5h; then calcined at 700°C for 4h, and then pulverized again after cooling at room temperature to 50μm to prepare nano-titanium dioxide pillared composite bentonite; then, under the protection of nitrogen, the composite bentonite was heated to 250°C and activated for 3h to prepare activated composite bentonite;
[0036] (2) Mixing nano-activated carbon and a 7 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:4, reflux reaction for 5 hours, washing with deionized water for 3 times after the reaction, and then drying in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; taking polyurethane acrylic resin and activated composite bentonite in a mass ratio of 1:3, stirring at a speed of 150 rpm for 10 minutes, adding 1.5 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; preparing an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, wherein the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2 wt%, the concentration of urea is 0.5 wt%, and the concentration of polyvinyl alcohol is 0.4 wt%, and then slowly adding the repair solution to the aqueous solution, the repair solution and the aqueous solution are mixed. The mass ratio of urea and formaldehyde to the repair liquid is 2:10, and it is stirred at 800 rpm for 40 minutes to form a uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40wt% according to a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then magnetically stirred at 70°C for 1 hour, and the stirring speed is 400 rpm. 1.5wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:2, and 3wt% of diphenol and 5wt% of ammonium chloride are added, and then the temperature is slowly raised to 60°C. After reacting for 5 hours, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12 hours to obtain self-healing microcapsules;
[0037] (3) The self-healing microcapsules were added to WSR618 epoxy resin at a specified mass fraction of 10%, and then DETA curing agent and aminopropyl triethoxysilane were added. The mass ratio of epoxy resin, DETA curing agent and aminopropyl triethoxysilane was 25:2:0.8. After stirring at 250 rpm for 20 min, the anti-cracking and high-durability coating was prepared by vacuum degassing at 0.085 MPa.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 and Example 2 is that steps (1) and (2) are different. Steps (1) and (2) are changed to: (1) crushing bentonite to 35 μm, and then heating the composite bentonite to 225° C. under the protection of nitrogen and activating for 2 h to obtain activated bentonite;
[0040] (2) Mix nano-activated carbon and 7 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:3, reflux and react for 5 hours, wash with deionized water three times after the reaction, and then dry in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; take polyurethane acrylic resin and activated bentonite at a mass ratio of 1:2, stir at 150 rpm for 10 minutes, add 1wt% 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; prepare an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, wherein the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2wt%, the concentration of urea is 0.5wt%, and the concentration of polyvinyl alcohol is 0.4wt%, and then slowly add the repair solution to the aqueous solution, and the mass ratio of the repair solution to the aqueous solution is 1. 5:10, stirring at 800 rpm for 40 min to form a uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40 wt% in a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then magnetically stirred at 70°C for 1 h, with a stirring speed of 400 rpm, and 1 wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1.5, and 3 wt% of m-diphenol and 5 wt% of ammonium chloride are added, and then the temperature is slowly raised to 55°C. After reacting for 4 h, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12 h to obtain self-healing microcapsules; the remaining steps are the same as those in Example 2.
[0041] Comparative Example 2
[0042] The difference between Comparative Example 2 and Example 2 lies in the difference in steps (1) and (2). Steps (1) and (2) are changed to: (1) adding butyl titanate to anhydrous ethanol, stirring at a speed of 500 rpm for 1 hour to mix uniformly to form a butyl titanate / ethanol solution, then dropping the butyl titanate / ethanol solution into a 1 mol / L nitric acid aqueous solution, wherein the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:11:1.4, and mixing and reacting by vigorously stirring at a speed of 3000 rpm for 20 minutes; adjusting the mixture with a 1 mol / L sodium hydroxide aqueous solution; pH to 2, stirring at 500 rpm for 30 minutes to obtain a mixed solution; taking bentonite, fully soaking it with deionized water at a mass ratio of 1:1, adding it to the mixed solution, so that the molar ratio of bentonite to butyl titanate is 10:1, stirring at 500 rpm for 2 hours, filtering it to separate the solid and liquid, washing the solid with deionized water 4 times, and then drying it at 60°C for 5 hours; then calcining it at 550°C for 4 hours, cooling it at room temperature, and crushing it again to 35μm to prepare a composite bentonite supported by nano-titanium dioxide;
[0043] (2) Mix nano-activated carbon and 7 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:3, reflux and react for 5 hours, wash with deionized water three times after the reaction, and then dry in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; take polyurethane acrylic resin and composite bentonite at a mass ratio of 1:2, stir at 150 rpm for 10 minutes, add 1wt% 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; prepare an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, wherein the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2wt%, the concentration of urea is 0.5wt%, and the concentration of polyvinyl alcohol is 0.4wt%, and then slowly add the repair solution to the aqueous solution, and the mass ratio of the repair solution to the aqueous solution is 1. 5:10, stirring at 800 rpm for 40 min to form a uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40 wt% in a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then magnetically stirred at 70°C for 1 h, with a stirring speed of 400 rpm, and 1 wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1.5, and 3 wt% of m-diphenol and 5 wt% of ammonium chloride are added, and then the temperature is slowly raised to 55°C. After reacting for 4 h, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12 h to obtain self-healing microcapsules; the remaining steps are the same as those in Example 2.
[0044] Comparative Example 3
[0045] The difference between Comparative Example 3 and Example 2 is that step (2) is different, and step (2) is changed to: take polyurethane acrylic resin and activated bentonite in a mass ratio of 1:2, mix them, stir them at a speed of 150 rpm for 10 min, add 1 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to prepare a repair solution; prepare an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2 wt%, the concentration of urea is 0.5 wt%, and the concentration of polyvinyl alcohol is 0.4 wt%, and then slowly add the repair solution to the aqueous solution, the mass ratio of the repair solution to the aqueous solution is 1.5:10, stir at a speed of 800 rpm, and stir until the mixture is uniform. The mixture was stirred for 40 minutes to form a uniformly dispersed water-in-oil core material; urea and formaldehyde were prepared into a mixed aqueous solution with a concentration of 40 wt% according to a molar ratio of 1:2, and a sodium hydroxide aqueous solution with a concentration of 6 mol / L was added to adjust the pH of the mixed aqueous solution to 8, and then the mixture was magnetically stirred for reaction at 70°C for 1 hour at a stirring speed of 400 rpm to form a prepolymer; the prepolymer was added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid was 1:1.5, and 3 wt% of m-diphenol and 5 wt% of ammonium chloride were added, and then the temperature was slowly raised to 55°C. After reacting for 4 hours, the solid was carefully taken out, washed twice with deionized water, and dried at room temperature for 12 hours to obtain self-healing microcapsules; the remaining steps were the same as those in Example 2.
[0046] Comparative Example 4
[0047] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: take polyurethane acrylic resin and activated bentonite in a mass ratio of 1:2, mix them, stir them at 150 rpm for 10 min, add 1 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to prepare a repair solution; prepare an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, the concentration of sodium dodecylbenzene sulfonate in the aqueous solution is 2 wt%, the concentration of urea is 0.5 wt%, and the concentration of polyvinyl alcohol is 0.4 wt%, then slowly add the repair solution to the aqueous solution, the mass ratio of the repair solution to the aqueous solution is 1.5:10, stir at 800 rpm for 40 min to form a uniform A uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40wt% in a molar ratio of 1:2, a sodium hydroxide aqueous solution with a concentration of 6mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then magnetically stirred for reaction at 70°C for 1h at a stirring speed of 400rpm, and 1wt% of nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1.5, and 3wt% of m-diphenol and 5wt% of ammonium chloride are added, and then the temperature is slowly raised to 55°C. After reacting for 4h, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12h to obtain a self-healing microcapsule; the remaining steps are the same as those in Example 2.
[0048] Comparative Example 5 (without adding silane coupling agent)
[0049] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: adding self-repairing microcapsules to WSR618 epoxy resin at a specified mass fraction of 5%, and then adding DETA curing agent, the mass ratio of epoxy resin to DETA curing agent is 25:2, stirring at 250 rpm for 20 minutes, and vacuum degassing at 0.085 MPa to obtain a crack-resistant and highly durable coating; the remaining steps are the same as Example 2.
[0050] Effect example
[0051] Table 1 below shows the performance analysis results of a crack-resistant and highly durable coating using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0052] Table 1
[0053] Crack situation Self-repair efficiency (%) Example 1 No cracks 87.1 Example 2 No cracks 87.6 Example 3 No cracks 87.2 Comparative Example 1 Small cracks 66.1 Comparative Example 2 Almost no cracks 73.2 Comparative Example 3 Small cracks 56.4 Comparative Example 4 Almost no cracks 76.5 Comparative Example 5 Almost no cracks 80.4
[0054] From the comparison of the experimental data of the self-repairing efficiency of the embodiment and the comparative example, it can be found that the present invention uses activated composite bentonite and polyurethane acrylic resin as core materials and modified urea-formaldehyde resin as wall materials to prepare microcapsules with self-repairing effect, which are added to the coating as fillers; when the coating is aged or subjected to external forces to produce fine cracks, the wall material modified urea-formaldehyde resin cracks to release the core material therein to repair; the composite bentonite is supported by nano-titanium dioxide pillars in the interlayer structure of the bentonite, which can make the bentonite more stable to prevent further cracking on the one hand, and on the other hand act as a photocatalyst from The internal catalysis of polyurethane acrylic resin begins, so that the core material is released and irradiated with external ultraviolet rays for curing. During the slow curing, titanium dioxide can absorb other organic pollutants and decompose other organic pollutants. At the same time, bentonite will expand to a certain extent due to contact with water molecules in the air, and fit fine cracks of different sizes to a greater extent. The activated bentonite is chemically combined with the light-cured polyurethane acrylic resin due to the hydroxyl groups on the surface, and then combined with the layered structure of bentonite due to curing and cross-linking, forming a stable and tight repair agent, so that the coating has a self-repairing effect, thereby improving the durability of the coating. The modified urea-formaldehyde resin used in the present invention is added to the urea-formaldehyde resin preparation process with oxidized nano-activated carbon. The active groups generated by oxidation can react with the methylol in the urea-formaldehyde resin to increase the cross-linking degree of the resin, and the activated carbon can not only adsorb free formaldehyde during the preparation process, but also make the urea-formaldehyde resin wall material have a light-shielding effect, so that the microcapsule core material is photocured and cross-linked after being released, thereby improving the durability. From the comparison of the experimental data of the cracking conditions of the embodiment and the comparative example, it can be found that the present invention improves the dispersibility of the self-repairing microcapsules through the silane coupling agent, so that they are evenly distributed in the coating with epoxy resin as the raw material, thereby improving the anti-cracking performance of the coating.
[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A crack-resistant and highly durable coating, characterized in that: The coating is prepared by adding self-made self-repairing microcapsules as fillers into epoxy resin.
2. The crack-resistant and highly durable coating according to claim 1, characterized in that: The self-made self-repairing microcapsules are prepared by using activated composite bentonite and polyurethane acrylic resin as core materials and modified urea-formaldehyde resin as wall materials to prepare microcapsules with self-repairing effect.
3. The crack-resistant and highly durable coating according to claim 2, characterized in that: The modified urea-formaldehyde resin is prepared by adding oxidized activated carbon to urea-formaldehyde resin.
4. A method for preparing a crack-resistant and highly durable coating, characterized in that: The method comprises the following preparation steps: (1) Add butyl titanate to anhydrous ethanol, stir at 500 rpm for 1 hour to mix evenly to form a butyl titanate / ethanol solution, then dropwise add the butyl titanate / ethanol solution to a nitric acid aqueous solution, vigorously stir at 3000 rpm for 20 minutes to allow a mixing reaction; adjust the pH to 1-3 with a 1 mol / L sodium hydroxide aqueous solution, and stir at 500 rpm for 30 minutes to obtain a mixed solution; take bentonite, fully soak it with deionized water at a mass ratio of 1:1, , add it to the mixed solution, stir at 500rpm for 2h, filter it to separate the solid and liquid, wash the solid with deionized water for 3-5 times, and then dry it at 60℃ for 5h; then calcine at 400-700℃ for 4h, cool at room temperature and crush it again to 20-50μm to prepare nano-titanium dioxide pillared composite bentonite; then heat the composite bentonite to 200-250℃ under the protection of nitrogen, activate it for 1-3h, and prepare activated composite bentonite; (2) Mixing nano-activated carbon and nitric acid aqueous solution at a solid-liquid ratio of 1:2-4 and refluxing for 5 hours, washing with deionized water for 3 times after the reaction, and then drying in an oven at 100°C for 8 hours to obtain oxidized nano-activated carbon; taking polyurethane acrylic resin and activated composite bentonite at a mass ratio of 1:1-3, mixing them at a speed of 150 rpm for 10 minutes, adding 0.5-1.5 wt% of 2-hydroxy-2-methyl-1-phenylacetone to the mixture to obtain a repair solution; preparing an aqueous solution containing sodium dodecylbenzene sulfonate, urea and polyvinyl alcohol, and then slowly adding the repair solution to the aqueous solution, the mass ratio of the repair solution to the aqueous solution is 1-2:10, stirring at a speed of 800 rpm for 40 minutes to form a uniform solution. A uniformly dispersed water-in-oil core material; urea and formaldehyde are prepared into a mixed aqueous solution with a concentration of 40wt% in a molar ratio of 1:2, a sodium hydroxide aqueous solution with a concentration of 6mol / L is added to adjust the pH of the mixed aqueous solution to 8, and then the mixture is magnetically stirred at 70°C for 1h at a stirring speed of 400rpm, and 0.5-1.5wt% of oxidized nano-activated carbon is added while stirring to form a prepolymer; the prepolymer is added to the water-in-oil core material so that the mass ratio of the prepolymer to the repair liquid is 1:1-2, and 3wt% of m-diphenol and 5wt% of ammonium chloride are added, and then the temperature is slowly raised to 50-60°C, and after reacting for 3-5h, the solid is carefully taken out, washed twice with deionized water, and dried at room temperature for 12h to obtain self-healing microcapsules; (3) The self-healing microcapsules were added to WSR618 epoxy resin at a specified mass fraction of 1 to 10%, and then DETA curing agent and aminopropyl triethoxysilane were added. After stirring at 250 rpm for 20 min, the bubbles were vacuum degassed at 0.085 MPa to obtain a crack-resistant and highly durable coating.
5. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: The concentration of the nitric acid aqueous solution in step (1) is 1 mol / L.
6. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: In the step (1), the molar ratio of butyl titanate, anhydrous ethanol and nitric acid is 1:6 to 16:1.
4.
7. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: In the step (1), the molar ratio of bentonite to butyl titanate is 5 to 15:
1.
8. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: The concentration of the nitric acid aqueous solution in the step (2) is 7 mol / L.
9. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: In the aqueous solution of sodium dodecylbenzenesulfonate, urea and polyvinyl alcohol in step (2), the concentration of sodium dodecylbenzenesulfonate is 2 wt %, the concentration of urea is 0.5 wt %, and the concentration of polyvinyl alcohol is 0.4 wt %.
10. The method for preparing a crack-resistant and highly durable coating according to claim 4, characterized in that: In the step (3), the mass ratio of epoxy resin, DETA curing agent and aminopropyltriethoxysilane is 25:2:0.4-0.8.
Citation Information
Patent Citations
Preparation method of electrical insulating layer material with micro-discharge defect self-repairing function
CN104356596A
Preparation method for electric insulating layer material with photoinduced self-repair function for microdischarge defects
CN104610703A
Self-healing microcapsule and preparation method thereof, paint, coating and epoxy resin composite material
CN107159070A
Self-repairing organic fluorine-silicon modified polyurethane waterproof coating and preparation method thereof
CN111826075A
Preparation method and application of self-repairing microcapsule
CN112210122A